LEARNING STRATEGY FOR THE ENHANCEMENT OF SUNDANESE SINGERS’ EXPERTISE AND COMPETENCY: SHIFTING FROM THE “NGABEO” TO THE “PRALAGAM” SYSTEM - Sumiyana, Sumiyana; Fitriasari, Paramitha Dyah; Asriningsih, Rani (Jurnal Industri Kreatif dan Inovatif, 2024)
This study investigates two competing systems for teaching Sundanese singers to achieve better performances. It argues that the new method, named Pralagam, is better for novice Sundanese singers than the Ngabeo system. The supremacy of the Pralagam system for teaching Sundanese singers is in the rigid procedures for their occupational and cognitive-behavioral practices. In the Pralagam system, most of the Sundanese singers’ time is spent mastering the optimal distinctiveness of the musical scale, vocalizing, cords, and practicing. However, the Ngabeo method does not emphasize these systems; it stresses practice only. This research took into account a field- experimental design, which compared the Ngabeo and Pralagam teaching methods for trainee Sundanese singers. It disclosed pieces of evidence about the learning process and the quality of the song’s output when Sundanese singers were practicing a song. This conclusion is also supported by the qualitative system, which comprehended that the Pralagam system is a unique learning system. This uniqueness is in its person-environment-occupation, treatment-fit, and low error methods. This study, therefore, recommends that the learning system should be shifted from Ngabeo to Pralagam. It infers that Sundanese singers would be better singers if they practice using the Pralagam system.